Why Countries Compete in Ad Valorem Instead of Unit Capital Taxes - Marco Runkel; Magnus Hoffmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper contributes to resolving the puzzle that in practice most countries use ad valorem (corporate income) taxation, while a large part of the tax competition literature views business taxes as unit (wealth) taxation. We point to the dual role that corporate taxation plays in attracting mobile capital, on the one hand, and in absorbing economic rents, on the other hand. In contrast to the previous literature, we show (i) that detrimental tax competition may be less severe in a system of ad valorem taxes than in a system of unit taxes and (ii) that ad valorem taxation may be the equilibrium outcome in a decentralized world where countries decide themselves on the tax system. Interestingly, the decentralized choice of the ad valorem system may be a prisoner's dilemma since the countries' welfare may be higher if they choose unit taxes.
Keywords: H21; H25; H77; 330